Potensi Ekstrak Buah Cabai Merah Keriting (Capsicum annum var. Longum) sebagai Antioksidan dan Antibakteri - I Gusti Bagus Teguh Ananta; Dewa Gede Anom Anjasmara (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2022)
Chili (Capsicum annum var. Longum) is a horticultural plant that is widely used as raw material for the food and pharmaceutical industry. Generally, chili fruit contains phenolic chemical compounds of flavonoid and capcaisinoid compounds. Bioactive compounds in chili such as phenols, flavonoids and capsaicinoid have a positive relationship to antioxidant and antimicrobial activity. Capsicum annum var. Longum contains secondary metabolites such as alkaloids, phenols, flavonoids, tannins and saponins. The total phenol content is 0.81% (807.76 mg GAE/100 g). The total content of flavonoids is 5.64% (5646.08 mg QE/100 g). Antioxidant activity was carried out using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method with an IC50 value of 505.35 ppm. Antibacterial activity was carried out by disc diffusion method with the growth inhibition of Escherichia coli bacteria of 8.56 mm and Staphylococcus aureus of 3.55 mm.